Eyelid Swelling and Subconjunctival Infiltration as Ophthalmic Manifestations in a Child with Idiopathic Hypereosinophilic Syndrome - Kim, Jeong-Ah; Kim, Namju; Choi, Hyoung-Soo; Choung, Ho-Kyung; Khwarg, Sang-In (Korean journal of ophthalmology, 2018)
KCI Citation Count: 0